Income tax deduction of commuting expenses and tax funding in an urban CGE study: the case of German cities - Georg Hirte; Stefan Tscharaktschiew (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2011)
Germany like many other European countries subsidize commuting by granting the right to deduct commuting expenses from the income tax base. This regulation has often been changed and has regularly been under debate during the last decades. The pros (e.g. causing efficiency gains with respect to the spatial allocation of labor) and cons (e.g. causing urban sprawl) are well documented. Nonetheless, there is need for further research. For reasons of tractability the few models applied in the tax deduction related literature are based on restrictive assumptions particularly concerning the design of the income taxation scheme and the structure of households (neglecting household heterogeneity) and, most importantly, they do not integrate labor supply and location decision problems simultaneously. Here, for the first time, those and more features are taken into account in a full spatial general equilibrium simulation approach calibrated to an average German city. This model is applied to calculate the impacts of tax deductions on an urban economy thereby considering different funding schemes. Our results suggest that the tax deduction level currently chosen is below the optimal level in the case of income tax funding. If a change in the tax base occurs, e.g. toward consumption tax or energy tax funding, the optimal size of the subsidy should be even higher. Furthermore, the different policy packages cause a very differentiated pattern regarding welfare distribution, environmental (CO2 emissions) and congestion effects. We also find surprisingly small effects on urban sprawl characterized by suburbanization of residences and jobs, increasing commuting distances and spatial city growth.
Keywords: C68; R12; R13; R14; R20; R51; 330; urban general equilibrium model; commuting subsidies; income tax deduction